Políticas públicas de comunicação no primeiro governo Dilma Rousseff (2011-2014) - Monteiro, Adriana Crisanto (2016)
This work has as main objective to analyze public communication policies in government Dilma Rousseff during period from 2011 to 2014. In this study, we try to make a historical overview over the presidential governments, making a panorama from the era of Vargas to the government's first mandate of president Dilma Rousseff. For this, we revisited the history of public communication policies, the laws that govern such policies, the institutions, the economy, the media, and how it all sets in the democratic State based on the rule of law. This survey was necessary so that we could answer to our research question, as we seek to understand: What is the role of the State and communications in the process of public communication policies? To answer this question, we try to understand the origin of the concepts: political and public separately, so from that, we could not only chart the semantics of the term, but also conceive it within our object of analysis. Already as corpus for this work, we elected Dilma Government's public policies between 2011-2014, grounded in 20 Public policy programs, laws and decrees created during her first mandate. From this point out, as a hypothesis, for our analysis, that even with significant advances, during her first mandate, Dilma Rousseff has showed a little developing in the communications field, with a number of obstacles ranging from the "old oligarchies" of families who control the media in the country, to the abuses and bureaucracies of governments and other socio-communicative and politicians agents. This fact has been pointed out in our analysis. So that this research can help changing this reality, we adopted as a base the qualitative and quantitative approach, in which the subject and researcher are integral parts of the construction process, giving them meaning, through the collected data sampling. In short, this work is justified by the fact that Brazil is a country that is undergoing a democratic transition, and this transition will not be complete until there is not a true transformation of the communication system, which has been perpetuated since military regime until nowadays. To base our analysis and understanding this theoretical discussion in the academic world we appeal to the authors Souza (2006), Bobbio (1984, 2012), Barros (2003), Bolaño (2008), Lima (1995, 2004), Gomes (2010 ) Althursser (1998), Poulantzas (1978), Liedtke (2002), Fausto Neto (1994), Thompson (1995) and other theorists of the areas of Communication and Public Policy. In this context socio-commnicative transformations this work is inserted, having as the main north to discussion of the importance of public policy communications, in addition to the media elite, guaranteeing the right to information to all citizens, based on the supreme principle of democracy and above all, the legitimacy of the facts, from the freedom of expression and, above all, with accessibility to public communication policies to ensure the break with the communication monopoly borders that prevails in our country.